Paresthesia of right encephalon creativity secondary to residency application anxiety - Denelle Mohammed (Canadian Medical Education Journal, 2019)
Applying to residency programs is a stressful time for any medical student. The finances, worries about the future, fear of not matching and being unable to repay loans can cause fleeting crippling moments for some students. As a residency applicant myself this year, and someone who has a fondness and passion for all things artistic, I sometimes find that the anxiety associated with application season can intermittently numb the creative side of my brain. It can even make my creative mind smaller because it is sometimes feels as though it is overtaken by more logical and practical thoughts. In addition, the lack of irises and pupils in the portrait show how far removed one’s mind can sometimes be from constructive emotion during this tough season of life.